PENGUATAN KARAKTER BERBASIS JATI DIRI BANGSA PADA PELAJAR NAHDLATUL ULAMA DAN IMPLIKASINYA TERHADAP KETAHANAN PRIBADI PEMUDA (Studi di Pimpinan Cabang IPNU Kabupaten Karanganyar, Provinsi Jawa Tengah) - Oktofianto, Dwi (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2018)
This research was studied the enforcement of IPNU PC national identity character in Karanganyar towards personal resiliences members. The enforcement of character based on IPNU PC national identity in Karanganyar is useful in preserving the trust and solidarity of citizens towards the nation state. The research method used was qualitative research with phenomenology approach. Data analysis techniques used by researchers were open coding and axial coding. The results showed that the enforcement of IPNU PC identity character in Karanganyar toward personal resiliences members was done by internalizing Pancasila values in science and khataman assemblies, Makesta (Loyalty of Members), and IPNU PC National Post-Exam Guidance (BPUN) in Karanganyar. The strengthening of IPNU PC's identity character in Karanganyar toward personal endurance of members starts from the stage of understanding (understand the true), ngrasa (feel good), and nglakoni (must be implemented). The implications to be a confident human being and firmly adhered to the principle, citizens who were active in the responsibilities of society, solid citizen living in harmony and togetherness, being an open citizen on the basis of kinship.Keywords: Character, Identity, Youth Organization and Personal Resilience.